THE THE CRISIS OF LEBANON'S POLITICAL SYSTEM IN A DYSFUNCTIONAL CONTEXT - E. N. Maksimova; E. E. Ryabtseva (Современная наука и инновации, 2023)
The article is devoted to the study of the dysfunctions of the political system of Lebanon, which have become sources of a large-scale crisis over the entire period of existence as an independent state. The methodology of this study is based on the theory of political systems, as well as the idea of dysfunctions as the main factors of destabilization of political systems. Dysfunctions are used as the main criteria for assessing the state of the political system: resource allocation in society, political governance, political participation and political representation. The analysis of the political system of Lebanon in accordance with the above criteria allowed us to give qualitative characteristics of the deep Lebanese crisis.